Pengaruh Pengawasan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Tetap pada PDAM TirtaTaman Kota Bontang - Disha Almira Fabiola (Perspektif Administrasi Publik dan hukum, 2025)
This study aims to analyze the effect of work supervision and work discipline on employee performance. This research method uses a quantitative method with an associative approach. Data obtained through distributing questionnaires to 54 permanent employees as respondents. Data analysis uses multiple linear regression analysis to determine the effect of the two independent variables (work supervision and work discipline) on the dependent variable (employee performance). The results of this study indicate that work supervision has a positive and significant effect on employee performance, which means that effective supervision can improve the performance of each individual. In addition, work discipline also has a positive and significant effect on performance, which indicates that employees with a high level of work discipline tend to work in accordance with applicable provisions. Simultaneously, work supervision and work discipline together have a significant effect on employee performance. Thus, the results of this study are expected to contribute to the management of PDAM Tirta Taman Kota Bontang in improving employee performance through supervision strategies and improving work discipline. This study concludes that work supervision and work discipline are key factors that can improve the performance of permanent employees at PDAM Tirta Taman Kota Bontang.